Implications of Virtual Reality in Arts Education: Research Analysis in the Context of Higher Education - Mariana-Daniela Go; Emilio Abad-Segura (MDPI AG, 2020)
Technological advances have posed a challenge in university learning ecosystems in terms of the application of immersive technologies that offer an educational and innovative framework to the student. The evolution of global research on this topic during the period 1980 to 2019 was studied. For this purpose, a bibliometric analysis of 1296 articles was applied, obtaining results of the scientific productivity of the journals, authors, institutions, and countries that contribute to this research. The evidence shows a growing interest, especially in the last three years, in the study of the application of virtual reality in higher education. The main subject area is Social Science. The most productive research institution is the Complutense University of Madrid. The United States is the country with the most publications and citations. In addition, The United States, Spain and the United Kingdom are the countries with the most international collaborations in their publications. The study detected five new directions for future research. The growing worldwide trend of scientific production demonstrates the interest in developing aspects of the use of virtual reality in arts education in the context of higher education. This study contributes to the academic, scientific and institutional discussion around the improvement of decision making based on the available information.